First report of cutaneous squamous cell carcinoma in an albino Central America Agouti (Dasyprocta punctata) in San Martin, Peru - Puicón N., Víctor (2023)
The case of an 8-year-old albino male Central America agouti (Dasyprocta punctata) bred in captivity in San Martín, Peru, with the presentation of a well-differentiated squamous cell carcinoma on the skin is reported. The appearance of a scabby skin lesion with macroscopic granulomatous characteristics was evidenced in the right temporal region recurrently after symptomatic treatment based on amoxicillin, dexamethasone, vitamin K and anti-myasis. The lesion rapidly evolved into an exophytic, expansive, haemorrhagic, and ulcerated infiltrative tumour mass. A cytological examination was performed, revealing a picture compatible with a malignant neoplasm of epithelial origin, and as a well-differentiated squamous cell carcinoma at the histopathological level when performing the necropsy. This report describes the first case of a cutaneous squamous cell carcinoma, both its macroscopic and microscopic characteristics, in an albino Central America Agouti n the San Martín region, Peru.